A Study on accelerating threat of Emerging Infectious Diseases (EIDs) and imperative for a proactive, interdisciplinary Global Health Security Framework - Dr. Kazi Kutubuddin (International Journal of Tropical Medicines, 2026)
Emerging Infectious Diseases (EIDs) represent one of the most critical and persistent threats to global health security in the 21st century. Driven primarily by the synergy of unprecedented human encroachment into wild habitats, climate change-induced ecological disruption, accelerated international travel, and antimicrobial resistance, the frequency and severity of zoonotic spillover events are rapidly increasing. Traditional, reactive public health measures—focused on containment after an emergence—have repeatedly proven insufficient, leading to catastrophic global consequences, as evidenced by recent pandemics and ongoing epidemics. This study argues that mitigating the perpetual threat of EIDs requires a fundamental paradigm shift from response to prediction and prevention. The core strategy must be rooted in the One Health framework, integrating human, animal, and environmental surveillance systems into a single, cohesive, intelligence-driven architecture. Key prerequisites include preemptive pathogen discovery, robust community-level diagnostics, equitable vaccine and therapeutic access, and the immediate prioritization of ecological preservation as a core public health mandate. Failure to adopt this proactive posture guarantees continued cycles of crisis, economic disruption, and avoidable mortality.
Keywords: Climate change; Emerging infectious diseases; Global Health Security; One Health; Predictive Epidemiology; Surveillance; Zoonotic spillover